The African agricultural revolution from its margins: concentration and relegation in Northern Mozambique - (:unkn) unknown (My University, 2018)
At the end of the 2000s, numerous African States adopted new agricultural policies and initiatives promoting food production and security. The Comprehensive Africa Agriculture Development Programme (CAADP, Map 1) has been one of the most ambitious intervention, pushing for increased agricultural productivity and calling for private and public investments to focus on the most promising spaces and farmers. Its effects on the ground are assessed based on the case of Northern Mozambique, a marginal space targeted by a development corridor and several investments (Map 2). I document how the interventions have concentrated on certain spaces and farmers and forsaken others. The mismatch between the expectations and the materializations has fed tensions between inhabitants, investors and administrations, both in invested and neglected spaces. Documenting the African agricultural revolution from its margins shows how structural and direct violence emerge from interactions with contemporary politics and previous exclusions.
Keywords: African Research